Pastoril: uma educação celebrada no corpo e no riso - Vieira, Marcílio de Souza (2010)
By means of the Pastoral one an Education celebrated in the body and the laugh, visible is unmasked by means of cançonetas and of the licentious gesticulations of the jokers of this idleness. For such, we support ourselves in the phenomenological of Merleau-Ponty, the tradition and transmission of the verbal as it is conceived by Paul Zumthor, as well as in the phenomenology of the memory of the jokers and in the studies of cultural history and the philosophy of the body. The objective research to argue the body and the laugh as learning of the culture, as well as carrying through the production of a cartography of the potiguar pastoral ones, in the direction to argue the elements of the licentious gesticulations for the look and of cançonetas for hearing. The research is of phenomenological nature and when appealing the Phenomenology as an attitude, recognizes our look on the phenomenon, what if we show for while searching citizens and we assume the reduction and the lived world as methodological boarding to think the searched phenomenon. As he was evidenced in this study, one searched to dimensional the reach of a reflection centered in the body and the laugh through the listening of cançonetas of the Pastoral one and the vision through the licentious gestures; a reflection centered in the body of the joker of Pastoral